Impact of Marketing, Sales and Innovations on Business Performance Analysis in Intellectual Capital Research: Latvia, Estonia and Lithuania (Marketing i Menedžment Innovacij)
Intellectual capital components’ meta system has exploded in the past decade following the four decades of intellectual capital research evolution, followed by wide discussions on definitions, measurements, reporting, impact analysis, etc. The evolution of IC research has been divided into four stages, although the borders between them are fluid and the exchange of ideas has grown in all directions at tremendous speed since the end of the 1990s. The intellectual capital theory has evolved from the resource-based view, competence-based view, and knowledge-based view. Intellectual capital, a new term, appeared in the 1990s and, in essence, coincided with the concept of intangible assets. In particular, researchers agree that the terms "intangible assets", "trademark", "good repute", and "intellectual property" in accounting and valuation activities do not cover everything that should be included in the new concept. It is about using intangible assets as a management object to increase the value of the company by involving previously unused reserves such as knowledge, information technology, customer satisfaction, etc. There is no unified definition; therefore, there is flexibility in using the term. Owing to its significance in the new sustainable reality, intellectual capital has become crucial for growing economies and has been recognized as a fundamental discipline that is thoroughly supported by practitioners and government structures worldwide. On the basis of the analysis of intellectual capital research, research questions can be defined in the form of a block-chain of the research areas, including a) terminology and definition b) components and classification; c) measurement and evaluation systems; d) value creation and, more recently, distortions; e) efficiency and effectiveness; f) reporting and disclosure; g) impact assessment; h) decision-making; and i) indication of contradictions and gaps for further research. The study used a sample of Nasdaq Baltic Issuers in Latvia, Lithuania and Estonia for the prepandemic period of 2012--2019 and collected 84 data units from the annexes to yearly financial statements explaining the cash flow and profit and loss statements of each. As companies are publicly listed, the financial measurements on the performance side were provided by the Morning star reports. Longitudinal regression analysis was applied for the impact analysis. The findings confirm that relational capital, measured as marketing and sales components with proxies for assets, sales revenue and value added, is significant in the case of ROA, ROE, ROS and RBS, which have positive impacts and do not affect the price‒earnings ratio of listed companies in Baltics. The exploratory longitudinal analysis confirms the data regarding the existence of a total of six factors in the pilot study that have an impact on the business performance indicators while showing different levels of significance, directions of impact and time scales, which highlights the unique findings of the current extended research on intellectual capital and is the first time that it has been applied in Baltic countries. Testing for the different proxies and moderate and control variables introduces new aspects to the analysis of the impact of resource deployment on business performance overall. Simultaneously, simplifying the model using composite aggregate ratios on both sides of the equation has created a precondition for optimizing impact models worldwide.